Retrospective Analysis of the Safety of Antibacterial Medicinal Products for Elderly Patients with Community-Acquired Lower Respiratory Tract Infections - G. I. Gorodetskaya; A. B. Prokofiev; S. Yu. Serebrova; E. Yu. Demchenkova; M. V. Zhuravleva; O. A. Demidova; T. V. Alexandrova; I. A. Mazerkina; E. A. Sokova; O. V. Muslimova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Cephalosporins are the empirical antibiotic therapy (ABT) of choice for patients with community-acquired pneumonia (CAP). When treated with antibiotics, elderly patients, especially those with comorbidities, are at higher risk of developing adverse drug reactions (ADRs).The aim of the study was to analyse data on the safety and efficacy of initial empirical ABT with cephalosporins in elderly patients over 75 years old with CAP admitted to multidisciplinary hospitals in Moscow.Materials and methods. The retrospective study included 305 medical records of patients with CAP admitted to three multidisciplinary hospitals in Moscow in 2017-2019 and prescribed initial mono- and/or combination ABT including a cephalosporin. Initial ABT was considered effective if the body temperature normalised within 48-72 h from the start of treatment. It was considered safe if there were no ADRs during hospital stay.Results. Mostly, patients were prescribed ceftriaxone monotherapy or ceftriaxone and azithromycin combination therapy. These ABT regimens were effective in 69.07% and 78.10% of the cases, respectively. Patients with severe CAP needed their initial ABT adjusted significantly more often than those with non-severe CAP. The initial ABT was changed for a number of reasons, including ineffectiveness, ADRs, abscesses formed as a complication of CAP, sputum culture results enabling causal ABT, secondary hospital-acquired infections, and exacerbated chronic infections. All patients had comorbidities, and the most prevalent were arterial hypertension (83.9%), coronary heart disease (45.6%), chronic heart failure (44.9%), cerebrovascular disease (40.9%), atrial fibrillation (26.9%), diabetes mellitus (21.3%), and chronic obstructive pulmonary disease (19.0%). Initial ABT was significantly more often considered ineffective in patients with chronic heart failure and cerebrovascular disease. The most common causative agent of CAP in the study population was Streptococcus pneumoniae (31.9%). In 16% of patients, the authors identified ADRs associated with the antibiotics used as initial therapy. The most common were diarrhoea, anaemia, leucopenia, and hepatopathy. Ceftriaxone was associated with ADRs in 11% of patients.Conclusions. The study results suggest that initial mono- and/or combination ABT including a cephalosporin is effective and relatively safe; therefore, this treatment option is expedient for elderly patients with CAP. For this population, the safety of ABT may be improved through the wider use of existing markers of ADRs and the identification of new ones.